Stock Volatility and the Levels of the Basis and Open Interest in Futures Contracts - CHEN, NAI‐FU; CUNY, CHARLES J.; HAUGEN, ROBERT A. (Journal of Finance, 1995)
ABSTRACT This article tests a theoretical model of the basis and open interest of stock index futures. The model is based on the differences between stock and futures in terms of investors' ability to customize stock portfolios and liquidity. Empirical evidence confirms the model's prediction that increased volatility decreases the basis and increases open interest.